Substitusi tepung kacang hijau (Vigna radiata) dan tepung ikan tuna (Thunnus sp) sebagai biskuit PMT ibu hamil terhadap kadar proksimat, nilai energi, kadar zat besi, dan mutu organoleptik - Miftahul Roifah; Maryam Razak; I Komang Suwita (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Nutrition problems in Indonesia are focused on the First 1000 Days of Life, which starts from the fetus in the mother's womb to toddlers aged 2 years. The targets to be intervened in this study are pregnant women. Where generally pregnant women have disorders such as anemia and Chronic Energy Deficiency. The disorder can be prevented by providing additional food using local ingredients. The purpose of this study was to obtain the right formulation of green bean flour biscuits and tuna flour for pregnant women PMT. This study uses a laboratory experimental research design with a completely randomized design study (CRD) using 3 levels of treatment, as many as 9 experimental units. P1 treatment level with the proportion of wheat flour: mung bean flour: tuna flour (75:15:10), P2 (65: 29: 6), and P3 (55: 41: 4). The results showed the substitution of mung bean flour and tuna flour had a significant influence on water content, ash content, protein content, fat content, iron content, aroma of biscuits. However, it gives no significant effect on carbohydrate levels. color, taste and texture. P2 treatment level is the best treatment.